Prevalence of Pain and Psychological Distress in High‐Performance Swimmers: Job Stress and Associated Factors – A Cross-Sectional Study - Martins, Lilian C X; Paiva, Jorge R; Freitas, Alexandre C; Miguel, Lester B; Maia, Flávio R C (Revista de Educação Física / Journal of Physical Education, 2018)
Introduction: High-performance athletes spend numerous hours per week training and therefore are more predisposed to suffer sports-related injury. Evidences show that depression and less severe degrees of emotional distress predict both: the onset of new episodes and persistence of pain. Objective: To examine the association of swimming training routines, job stress (effort-reward imbalance), overtraining-related subjective markers, and biological and sociodemographic factors with prevalence of pain and with psychological distress, in high-performance swimmers from the highest-level competition. Methods: Observational sectional study. Forty-two high-performance swimmers (N=42) from the most elevated competition level (World-class and Olympic) took part in the study as population census of the swimming athletes. Analyses were performed using c2, simple and multiple logistic regressions (via generalized linear models). Results: Prevalence of psychological distress was of 35.7%. Prevalence of pain was of 45.2% and there was significantly difference between men and women (p<0.001). Psychological, psychosocial, biological, socioeconomic and demographic factors were not associated with pain (p>0,05). Overtraining-related subjective markers and low reward were associated with psychological distress (p=0,020), but not with pain. Psychological distress and pain were associated with decreased performance and lower quality of life athletes. Conclusion: Few studies focused pain in high-performance athletes. The present study indicated that further attention is required in training routines, inside and outside the pool to prevent pain in high performance swimmers. Prevalência de dor e sofrimento psicológico em nadadores de alto rendimento: estresse no trabalho e fatores associados – um estudo seccional Introdução: Atletas de alto rendimento passam inúmeras horas por semana treinando e, portanto, estão mais predispostos a sofrer lesões relacionadas ao esporte. Evidências mostram que a depressão e graus menos graves de sofrimento emocional predizem ambos: o início de novos episódios e a persistência da dor. Objetivo: Examinar a associação de rotinas de treinamento em natação, estresse no trabalho (desequilíbrio esforço-recompensa) e outros fatores com prevalência de dor e sofrimento psíquico em nadadores de alto rendimento. Além disso, examinamos a relação de sofrimento psicológico e dor. Métodos: Estudo seccional observacional. Quarenta e dois nadadores de alto rendimento (N = 42) do nível competitivo mais elevado (World-Class e Olympic) participaram do estudo como amostra de conveniência. As análises foram realizadas usando c2, regressões logísticas simples e múltipla (via modelos lineares generalizados). Resultados: A prevalência de sofrimento psíquico foi de 35,7%. A prevalência de dor foi de 45,2% e houve diferença significativa entre homens e mulheres (p<0,001). Fatores psicológicos, psicossociais, biológicos, socioeconômicos e demográficos não foram associados à dor (p>0,05). Marcadores subjetivos relacionados ao excesso de treinamento e baixa recompensa foram associados com sofrimento psíquico (p=0,020), mas não com dor. Sofrimento psicológico e dor foram associados com a diminuição do desempenho e menor qualidade de vida atletas. Conclusão: É necessária maior atenção nas rotinas de treinamento, dentro e fora da piscina, para prevenir a dor em nadadores de alto desempenho.